2020
DOI: 10.3390/cryst11010008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Moisture Transport in Concrete

Abstract: Moisture with harmful ions penetrates into the interior of concrete, which causes deterioration of the concrete structure. In this study, a moisture saturation equilibrium relationship of concrete was tested under different temperatures and relative humidity conditions to develop moisture absorption and desorption curves. Based on experimental data and numerical simulation, a model of moisture transport in concrete was established. The results from the model indicate that the moisture absorption rate was lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…26 If taking into account that the heat flux from the atmosphere or the surface on which the concrete coupon is positioned and Knudsen diffusion, the contribution due to the vapor pressure is much larger than the effect of temperature or relative humidity. 46,50,51 Therefore, temperature and relative humidity at this scale (which is relevant for most scenarios; see introduction) will not dominate the evaporation process of liquid anhydrous ammonia from a porous network such as concrete. This work and the data shown in Figure 4 (diffusion-limited evaporation) and Figure 5 (limited or no effects due to temperature and relative humidity) support this claim.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 If taking into account that the heat flux from the atmosphere or the surface on which the concrete coupon is positioned and Knudsen diffusion, the contribution due to the vapor pressure is much larger than the effect of temperature or relative humidity. 46,50,51 Therefore, temperature and relative humidity at this scale (which is relevant for most scenarios; see introduction) will not dominate the evaporation process of liquid anhydrous ammonia from a porous network such as concrete. This work and the data shown in Figure 4 (diffusion-limited evaporation) and Figure 5 (limited or no effects due to temperature and relative humidity) support this claim.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, given the short distances that anhydrous ammonia must travel through the coupon, the expected mechanism of evaporation is via diffusion through the capillary to the surface 26 . If taking into account that the heat flux from the atmosphere or the surface on which the concrete coupon is positioned and Knudsen diffusion, the contribution due to the vapor pressure is much larger than the effect of temperature or relative humidity 46,50,51 . Therefore, temperature and relative humidity at this scale (which is relevant for most scenarios; see introduction) will not dominate the evaporation process of liquid anhydrous ammonia from a porous network such as concrete.…”
Section: Resultsmentioning
confidence: 99%
“…The fine aggregate is made of river sand. The measured water content is 4.8% (mass fraction), the fineness modulus is 2.6 (belongs to medium sand), the mud content is less than 1% (mass fraction), and the apparent density is 2.54 g/cm 3 . The mix proportions of cement paste (P-0.3, P-0.4, P-0.5) and mortar (M-0.3, M-0.4, M-0.5) are provided in Table 3.…”
Section: Adsorption and Desorption Experiments On Cement-based Materi...mentioning
confidence: 94%
“…Durability is one of the most prominent problems of cement-based materials. The transport of water in the pore network directly influences the mechanical (shrinkage, creep) and chemical (penetration of aggressive agents) degradation of cement-based materials [1][2][3][4][5]. The adsorptiondesorption curve can reflect the corresponding relationship between the equilibrium water content of porous materials and the relative humidity (RH) of the environment; thus, it is one of the major data used to evaluate durability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with rectangular and V-shaped cracks, the chloride diffusion process in cracked concrete with a tortuous crack was slower at the early immersion age, while the crack geometry had a marginal influence on the chloride penetration depth in cracked concrete during long-term immersion. Zhang et al [21] built a moisture saturation equilibrium relationship of concrete under different temperatures and relative humidity conditions to develop moisture absorption and desorption curves. They concluded that the moisture absorption rate was lower at higher temperatures and largely dependent on the saturation gradient, while the desorption was increased at higher temperatures and mostly affected by the saturation gradient.…”
mentioning
confidence: 99%